Relationship between tooth loss, low masticatory ability, and nutritional indices in the elderly: a cross-sectional study - Okamoto, Nozomi (BMC Oral Health, 2019)
BACKGROUND: Low masticatory ability and the resulting decrease in intake of masticable foods can result in undernutrition. The present study investigated the relationship between tooth loss, low masticatory ability, and nutritional indices in the elderly. METHODS: The data analyzed in this study were retrieved from the baseline data of the 2007 Fujiwara-kyo study, a prospective cohort study of community-dwelling elderly individuals. Subjects included 1591 men and 1543 women, both with a median age of 71 years. The maximum occlusal force was measured as an objective index of masticatory ability. Foods were divided into five groups based on hardness: Group 1 (bananas, etc.), 0.53 kg; Group 2 (boiled rice, etc.), 1.22 kg; Group 3 (raisins, etc.), 2.93 kg; Group 4 (raw carrots, etc.), 4.38 kg; and Group 5 (beef jerky), 6.56 kg. To obtain a subjective index of masticatory ability, a questionnaire-based survey was conducted to determine whether subjects could masticate foods within each group. As nutritional indices, serum albumin levels and body mass index (BMI) data were used. RESULTS: The median number of teeth was 21. The proportion of subjects for whom all five food groups were masticable showed a significant decrease in the number of teeth in both males and females. Logistic regression analysis showed that, after adjustment for confounders, no significant relationships were observed between the number of teeth and the masticatory ability with nutritional indices in males. In females, a maximum occlusal force of 100 to 300 N (OR = 1.65; 95% CI = 1.06–2.55) or less than 100 N (OR = 1.95; 95% CI = 1.15–3.31) showed a significant correlation with serum albumin levels below 4.4 g/dL (reference: 500 N or more). In addition, the masticability of all five food groups showed a significant correlation with BMI < 21.0 kg/m(2) (OR = 0.62; 95% CI = 0.46–0.85) in females. CONCLUSIONS: A low number of teeth was associated with low masticatory ability in both males and females. Low masticatory ability was associated with low plasma albumin levels and low BMI in females. Not smoking, maintaining grip strength, preventing cancer, and masticatory ability are important for preventing undernutrition.